The negotiation process of the EU-SA Trade, Development and Co-operation Agreement: a case of reference for the south?,The negotiation process of the European Union-South Africa Trade, Development and Co-operation Agreement: a case of reference for the south? - Pillay, Morgenie (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2003)
Overall the conclusions drawn about South Africa's negotiating style and tactics were arrived at by analysing a number of reports (that closely followed the evolution of the negotiations) and then paralleling this case study's findings with the conjectures made by the theoretical frameworks (i.e. works by Putnam, Zartmann and Churchmann) about how negotiations proceed. In the final analysis, the findings of this case are intended to provide insight for the south about how to approach any future trade negotiations with the North (or more specifically with the EU).
Keywords: South Africa -- Foreign economic relations -- European Union countries; European Union countries -- Foreign economic relations -- South Africa; South Africa -- Commerce -- European Union countries; European Union countries -- Commerce -- South Africa; Free trade -- South Africa; Trade regulation -- South Africa